The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.29173/irie229
|View full text |Cite
|
Sign up to set email alerts
|

Access to Information is (Not) a Universal Right in Higher Education: Librarian Ethics and Advocacy

Abstract: As a profession, librarians have proclaimed an ethical duty to ensure access to information for all people. However, many barriers exist to fulfilling this duty, including varying levels of education and technology around the globe, the cost of obtaining research information, and the concentration of scholarly publishing in English. This article outlines these barriers, concluding with a call to action for librarians to advocate for multilingual Open Access, to foster international scholarly communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…As a result of this, many people remain uninformed about crucial matters that affect their lives; in fact, many people are frustrated by the challenge of acquiring the necessary information to solve problems. Bridges and McElroy (2015) observed that segmented access to information can be very dangerous and have severe consequences. This was substantiated by Dahn et al (2015) who claimed the threat of Ebola had been identified as far back as 1982 but the research was locked up in expensive journal archives inaccessible to health practitioners in Liberia.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of this, many people remain uninformed about crucial matters that affect their lives; in fact, many people are frustrated by the challenge of acquiring the necessary information to solve problems. Bridges and McElroy (2015) observed that segmented access to information can be very dangerous and have severe consequences. This was substantiated by Dahn et al (2015) who claimed the threat of Ebola had been identified as far back as 1982 but the research was locked up in expensive journal archives inaccessible to health practitioners in Liberia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the characteristics of information is that it is abundant, unlike other economic resources, which are scarce. Despite this, many barriers exist to hinder its accessibility such as education, technology, cost, and culture (Bridges and McElroy, 2015). As a result of this, many people remain uninformed about crucial matters that affect their lives; in fact, many people are frustrated by the challenge of acquiring the necessary information to solve problems.…”
Section: Universal Access To Information and Knowledgementioning
confidence: 99%